Characterization of iRGD-Ligand Modified Arginine-Histidine-Rich Peptides for Nucleic Acid Therapeutics Delivery to αvβ3 Integrin-Expressing Cancer Cells - Anna Egorova; Alexander Selutin; Marianna Maretina; Sergei Selkov; Vladislav Baranov; Anton Kiselev (Pharmaceuticals, 2020)
Efficient and specific delivery of nucleic acid (NA) therapeutics to tumor cells is extremely important for cancer gene therapy. Various therapeutic strategies include delivery of DNA-therapeutics such as immunostimulatory or suicide genes and delivery of siRNA-therapeutics able to silence expression of cancer-related genes. Peptides are a promising class of non-viral vehicles which are biodegradable and can efficiently condense, protect and specifically deliver NA to the cells. Here we designed arginine-histidine-rich peptide carriers consisting of an iRGD ligand to target αvβ3 integrins and studied them as vehicles for DNA and siRNA delivery to cancer cells. Combination of iRGD-modified and unmodified arginine–histidine-rich peptides during NA complexation resulted in carriers with different ligand contents. The NA-binding and protecting properties in vitro transfection efficiency and cytotoxicity of the DNA- and siRNA-polyplexes were studied and the most efficient carrier RGD1 was determined. The ability of the peptides to mediate specific intracellular uptake was confirmed inhuman cervical carcinoma (HeLa), human kidney (293T) and human pancreatic (PANC-1) cell lines with different αvβ3 integrins surface expression. By means of RGD1 carrier, efficient delivery of the herpes simplex virus (HSV-1) thymidine kinase gene to PANC-1 cells was demonstrated. Subsequent ganciclovir treatment led to a reduction of PANC-1 cells’ viability by up to 54%. Efficient RNAi-mediated down-regulation of GFP and VEGFA gene expression was achieved in MDA-MB-231-GFP+ breast cancer and EA.hy926 endothelial cells, respectively, by means of RGD1/siRNA polyplexes. Here we demonstrated that the peptide carrier RGD1 can be considered as promising candidate for development of NA therapeutics delivery systems useful in cancer gene therapy.